2011
DOI: 10.1111/j.1463-1318.2011.02584.x
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity and bariatric surgery: a systematic review of associations with defecatory dysfunction

Abstract: Few studies have assessed the correlations between obesity and defecatory function and the effect of bariatric surgery. Studies were often not well controlled and used non-uniform instruments to assess bowel function. Obesity appears to be correlated with higher rates of faecal incontinence and diarrhoea. The effects of bariatric surgery on these conditions are not well defined. Well-controlled studies correlating outcome with physiological pelvic floor function are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 31 publications
(153 reference statements)
0
33
0
2
Order By: Relevance
“…(24) Obesity has also been associated with fecal incontinence, which affects 16–68% of obese individuals. (25) The prevalence of fecal incontinence has also been shown to decrease after weight loss after bariatric surgery (19), further emphasizing the importance of obesity as a modifiable risk factor. The association of obesity with pelvic floor disorders highlights the importance of addressing weight loss in obese women and of screening for these disorders in overweight and obese women.…”
Section: Discussionmentioning
confidence: 99%
“…(24) Obesity has also been associated with fecal incontinence, which affects 16–68% of obese individuals. (25) The prevalence of fecal incontinence has also been shown to decrease after weight loss after bariatric surgery (19), further emphasizing the importance of obesity as a modifiable risk factor. The association of obesity with pelvic floor disorders highlights the importance of addressing weight loss in obese women and of screening for these disorders in overweight and obese women.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] There is also higher prevalence (16-68%) of fecal incontinence in obese women. 19 With the measures to decrease weight following bariatric surgery, the prevalence of fecal incontinence decreased significantly. 16 This association between obesity and urinary and fecal incontinence shows that weight loss in obese and overweight women is important aspect in preventing and treating them.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a range of results from no association to up to 69% of obese subjects having fecal incontinence. 37,108 Obesity is emerging as a potentially modifiable risk factor in fecal incontinence, 109 and obesity (BMI ≥ 30 kg/m 2 ) was a significant risk factor for increased functional difficulty/dependence as a result of fecal incontinence. 110 …”
Section: Anal Canal and Pelvic Floormentioning
confidence: 99%